Comparative Performance of Unbuffed and Buffed Automobile Discarded Tyres Used in Camel Cart - Tiwari, Ghanshyam; Sharma, Ajay Kumar (Annals of Arid Zone, 2016)
Two different types of selected automobile discarded tyres, namely unbuffed and buffed, 9.00 Â·to 20.00 size were compared for their performance. Tests were conducted in sand under controlled soil bin condition at different levels of compaction (3.4 to 4.5 MPa m,l), intlation press:Jre (69 to 345 kPa) with normal load (200 to 1000 daN). ButTed tyre indicated 5 to 40% less rolling resistance than the same size of unbuffed tyre in the test range of different parameters.